STEM career: essential factors for students to achieve success in STEM (supportive individuals, skills/abilities, motivational factors) - Dogaru, Mariana; Negreanu, Mirela Cristina; Pisicǎ, Olivia; Pîrvu, Alina Florentina (Frontiers in Education, 2025)
In Romania, where STEM enrollment stands at 26% of tertiary students compared to the EU average of 32%, understanding the factors that sustain student engagement is critical. This mixed-methods study examines motivations, wellbeing, and gender stereotypes shaping STEM success among 548 students at a technical university from Bucharest. Through literature review, questionnaires, and interviews, analyzed via inferential statistics and thematic coding, findings reveal that intrinsic motivation (34.74%) and career opportunities (36.16%) drive major choices, 71.39% associate STEM engagement with enhanced wellbeing, and 42.8% perceive gender stereotypes, with girls reporting greater impact. Triangulated data highlight the need for mentorship, digital resources, and inclusive policies to support Romania's STEM aspirations. Limited to one institution, this study offers insights for educators and policymakers to foster equitable STEM education.